Does environmental heat stress impact physical and technical match-play characteristics in football? - Loxston, C.; Lawson, M.; Unnithan, V. (Science and Medicine in Football, 2019)
Purpose: To examine the impact of environmental heat stress conditions on physical and technical football match-play characteristics. Method: Data from 42 matches of 9 outfields, professional football players were collected in temperatures ranging from 13°C to 37°C and relative humidity ranging from 11% to 83%. Individual player data were only included if a player had played a full match (>90+ min) and had completed at least one full match in each of the four available environmental heat stress risk conditions of low, moderate, high and excessive. Results: Significant effects were observed for run speed (p = .001), high speed run (p = .041), high intensity (p = .023) and explosive (p = .001) distance covered, with run speed and explosive distance significantly decreasing in excessive compared to low environmental heat stress conditions. Similarly, the number of balls lost (p = .002) significantly decreased in excessive compared to low climatic conditions. Total and sprint distances were unaffected. Conclusion: Excessive environmental conditions may impact physical and to some degree technical match-play characteristics. A rational may be due to professional players employing pacing strategies to modulate their physical exertion in an attempt to control thermal strain and physical fatigue.